Commercial Sexual Exploitation of Children in the United States, 1997-2000 - Estes, Richard J. ([Verlag nicht ermittelbar], 2003)
This project undertook the systematic collection of first-generation data concerning the nature, extent, and seriousness of child sexual exploitation (CSE) in the United States. The project was organized around the following research objectives: (1) identification of the nature, extent, and underlying causes of CSE and the commercial sexual exploitation of children (CSEC) occurring in the United States, (2) identification of those subgroups of children that were at the greatest risk of being sexually exploited, (3) identification of subgroups of adult perpetrators of sex crimes against children, and (4) identification of the modes of operation and other methods used by organized criminal units to recruit children into sexually exploitative activities. The study involved surveying senior staff members of nongovernment organizations (NGOs) and government organizations (GOs) in the United States known to be dealing with persons involved in the transnational trafficking of children for sexual purposes. Part 1 consists of survey data from nongovernment organizations. These were local child and family agencies serving runaway and homeless youth. Part 2 consists of survey data from government organizations. These organizations were divided into local, state, and federal agencies. Local organizations included municipal law enforcement, county law enforcement, prosecutors, public defenders, and corrections. State organizations included state child welfare directors, prosecutors, and public defenders. Federal organizations included the Federal Bureau of Investigation, Federal Public Defenders, Immigration and Naturalization Service, United States Attorneys, United States Customs, and the United States Postal Service. Variables in Parts 1 and 2 include the organization's city, state, and ZIP code, the type of services provided or type of law enforcement agency, how the agency was funded, the scope of the agency's service area, how much emphasis was placed on CSEC as a policy issue or a service issue, conditions that might influence the number of CSEC cases, how staff were trained to deal with CSEC cases, how victims were identified, the number of children that experienced child abuse, sexual abuse, pornography, or other exploitation in 1999 and 2000 by age and gender, methods of recruitment, family history of victims, gang involvement, and substance abuse history of victims.